Mechanical Thrombectomy in Acute Ischemic Stroke: Effectiveness, Service Gaps, and Efforts to Optimize Access - M. Usama Royhul Azhar; Karina Dewi; Mery Krismanto (CV. Publikasi Indonesia, 2026)
Ischemic stroke is a global health burden, including in Indonesia, where the incidence and prevalence are very high. Although the treatment of ischemic stroke has advanced, mechanical thrombectomy is becoming a significant interventional procedure. This research aims to review the effectiveness, safety, and challenges of implementing mechanical thrombectomy in real clinical practice, as well as to analyze the factors influencing treatment outcomes. The literature review was conducted using a narrative approach, with articles selected from PubMed published between 2020–2025 in English, discussing thrombectomy in acute ischemic stroke, and available in full text. Articles not meeting these criteria, including those published before 2020, case reports, and literature reviews, were excluded. Of 1,171 articles, five met the criteria for analysis. Mechanical thrombectomy demonstrates high effectiveness with high recanalization rates, often surpassing those reported in clinical trials. However, these technical advances do not always correlate with improved patient quality of life due to changes in patient profiles, such as older age, moderate vascular occlusion, and delayed treatment. While the procedure is relatively safe, expanding patient criteria and systemic factors may increase the risk of mortality. Key challenges include limited access, lack of expertise, diagnostic barriers, financial constraints, and service gaps. Mechanical thrombectomy is an effective treatment for ischemic stroke, significantly improving recanalization rates. Long-term outcomes depend on factors such as treatment timeliness, case complexity, and patient age. To optimize benefits, improving workflows, expanding access to services, and tailoring treatment strategies to individual patient conditions are essential.